Cost Accounting, Principles and Managerial Applications (Book). - Sterling, Robert R.; Schaefer, Hadley P. (The Accounting Review, 1970)
Reviews the book "Cost Accounting, Principles and Managerial Applications," 2nd ed., by Gerald R. Crowningshield.